NEED FOR INNOVATION IN THE INDIAN KNOWLEDGE TRADITION - Chelani, Gomti (International Journal of Research -GRANTHAALAYAH, 2026)
The Indian knowledge tradition is one of the oldest and richest knowledge systems in the world. This tradition not only provides spiritual and philosophical perspectives but also makes significant contributions to the fields of science, mathematics, medicine, and art. The history of the Indian knowledge tradition spans the Vedas, Upanishads, Ayurveda, mathematics, astronomy, philosophy, and art. This tradition has been rich not only from a spiritual but also from a scientific perspective. In the present era of global competition and technological advancement, there is a need to revive this tradition with innovation, so that the heritage of ancient times can be kept alive, connected to the present, and made relevant and useful. This research paper attempts to discuss in detail this need, its scope, challenges, and potential solutions. Methodology This research paper attempts to draw conclusions based on the study of various research articles obtained from the internet, articles published in various journals, and books related to the Indian knowledge tradition.